Cell sheet engineering: Recreating tissues without biodegradable scaffolds - Yang, J.; Yamato, M.; Kohno, C.; Nishimoto, A.; Sekine, H.; Fukai, F.; Okano, T.
While tissue engineering has long been thought to possess enormous potential, conventional applications using biodegradable scaffolds have limited the field's progress, demonstrating a need for newmethods. We have previously developed cell sheet engineering using temperature-responsive culture dishes in order to avoid traditional tissue engineering approaches, and their related shortcomings. Using temperature-responsive dishes, cultured cells can be harvested as intact sheets by simple temperature changes, thereby avoiding the use of proteolytic enzymes. Cell sheet engineering therefore allows for tissue regeneration by either direct transplantation of cell sheets to host tissues or the creation of three-dimensional structures via the layering of individual cell sheets. By avoiding the use of any additional materials such as carrier substrates or scaffolds, the complications associated with traditional tissue engineering approaches such as host inflammatory responses to implanted polymer materials, can be avoided. Cell sheet engineering thus presents several significant advantages and can overcome many of the problems that have previously restricted tissue engineering with biodegradable scaffolds.
Keywords: CELL SHEET; TEMPERATURE-RESPONSIVE CULTURE DISH; BIODEGRADABLE SCAFFOLD; INFLAMMATION